Sex-specific dysregulation of the CX3CL1/CX3CR1 Axis following cocaine exposure: Translational evidence for a potential biomarker of abstinence - Porras-Perales, Oscar; Sánchez-Marín, Laura; Medina-Vera, Dina; Flores-López, María; Martín-Chaves, Laura; Boccalon, Milena; Requena-Ocaña, Nerea; García-Marchena, Nuria; Reviriego, Raquel; Santín-Núñez, Luis Javier; Martin-Fardon, Remi; Jiménez-Navarro, Manuel Francisco; et al. (ELSEVIER, 2025)
Cocaine disrupts neurotransmitter systems and promotes neuroinflammation by activating microglia and altering cytokine signaling. The CX3CL1/CX3CR1 axis is an essential signaling pathway for microglial regulation, may exhibit sex-specific responses to cocaine. In this study, male and female Wistar rats were exposed to acute (5, 15, or 30 mg/kg) or repeated (15 mg/kg/day for two weeks) cocaine. Gene expression of Cx3cl1 and Cx3cr1 was assessed in the amygdala and hippocampus, alongside plasma CX3CL1 concentrations. Additionally, plasma CX3CL1 concentrations were assessed in 88 abstinent patients with cocaine use disorder (CUD) and 30 matched healthy controls. Female rats exhibited significantly lower baseline mRNA expression of Cx3cl1 and Cx3cr1 in both brain regions compared with male rats. Acute cocaine induced dose- and time-dependent transcriptional changes, with female rats exhibiting more pronounced and sustained Cx3cl1 and Cx3cr1 expression changes compared with males. Repeated exposure produced sex-, region-, and abstinence-dependent regulations of Cx3cl1 and Cx3cr1, with persistent downregulation of Cx3cl1 and compensatory Cx3cr1 upregulation in female rats. In plasma, only male rats exhibited elevated CX3CL1 concentrations following cocaine exposure, particularly during early abstinence (i.e., 2 h–72 h). In humans, overall CX3CL1 concentrations did not differ between CUD patients and controls. However, CX3CL1 concentrations increased with abstinence duration, particularly in males (r = +0.34, p < 0.01), but not in females. These findings highlight sex-specific regulation of the CX3CL1/CX3CR1 axis in cocaine-induced neuroinflammation and suggest that plasma CX3CL1 concentrations may serve as a potential biomarker or contribute to a composite biosignature, together with other biomolecules, of CUD progression and abstinence. Considering sex differences, may enhance our understanding of addiction pathophysiology and inform targeted therapeutic strategies.
Keywords: Cocaína; Diferencias sexuales; Dimorfismo sexual en animales; Marcadores bioquímicos; Neurobiología; Adicción; Receptores de neurotransmisores; Abstinence; Biomarker; Cocaine; Fractalkine; Sexual dimorphism; Translational